2022
DOI: 10.3390/nu14040728
|View full text |Cite
|
Sign up to set email alerts
|

Bound Polyphenols from Red Quinoa Prevailed over Free Polyphenols in Reducing Postprandial Blood Glucose Rises by Inhibiting α-Glucosidase Activity and Starch Digestion

Abstract: Inhibiting α-glucosidase activity is important in controlling postprandial hyperglycemia and, thus, helping to manage type-2 diabetes mellitus (T2DM). In the present study, free polyphenols (FPE) and bound polyphenols (BPE) were extracted from red quinoa and their inhibitory effects on α-glucosidase and postprandial glucose, as well as related mechanisms, were investigated. HPLC-MS analysis showed that the components of FPE and BPE were different. FPE was mainly composed of hydroxybenzoic acid and its derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…This was probably due to the fact that, despite maintaining a similar energy intake between products consumed in the RD and the QD, quinoa has diverse nutrients that, as we have said, may imply lower glycemia [ 1 ]. Likewise, antioxidant molecules and protein nutrients are also related to the same glycemic response in the QD, as previously has been observed [ 6 , 32 , 33 ]. Conversely, carbohydrates, as we could expect, but also fats, especially monounsaturated fatty acids (MUFA), were associated with higher glucose concentrations in this diet.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This was probably due to the fact that, despite maintaining a similar energy intake between products consumed in the RD and the QD, quinoa has diverse nutrients that, as we have said, may imply lower glycemia [ 1 ]. Likewise, antioxidant molecules and protein nutrients are also related to the same glycemic response in the QD, as previously has been observed [ 6 , 32 , 33 ]. Conversely, carbohydrates, as we could expect, but also fats, especially monounsaturated fatty acids (MUFA), were associated with higher glucose concentrations in this diet.…”
Section: Discussionsupporting
confidence: 69%
“…Among other nutrients, phenolic compounds found in quinoa [ 2 , 3 ] show inhibitory effects on α-glucosidase and lipase activities [ 4 , 5 ] that are involved in sugar and lipid digestion in the digestive tract, respectively. Specifically, it has recently been observed that the polyphenols present in quinoa could have an effect on the reduction in postprandial blood glucose [ 6 ]. All this leads us to think that quinoa can be used to improve the profile of metabolic risk factors and help control type 2 diabetes (T2D) [ 3 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inhibitory activity depends on the structural peculiarities of the phenolic compounds. Recently, Zhang et al [ 61 ] reported that the fraction of bound polyphenolics of red quinoa composed mainly of ferulic acid more strongly inhibited α-glucosidase than the fraction of free polyphenolics consisting mainly of hydroxybenzoic acid and its derivatives; the former fraction inhibited α-glucosidase in an uncompetitive mode, while the latter one in a non-competitive mode. This was explained by the peculiarities of the interactions between ferulic acid and enzyme amino acid sites.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other than these nutrients, quinoa also contain rich healthbeneficial phytochemicals including polyphenols, saponins and phytosterols, etc. 9,10 Although some previous studies have reported the effects of cooking methods on fruits and vegetables, 2,5,11 studies about the comparison and effects of cooking methods on the polyphenols of quinoa in terms of their activities are yet to be seen. Thus, the present study used boiling, roasting and microwaving to cook black quinoa grains and extracted polyphenols from them.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoa has attracted increasing attention due to its nutritional features, such as rich fiber, vitamins, minerals and balanced essential amino acids 8 . Other than these nutrients, quinoa also contain rich health‐beneficial phytochemicals including polyphenols, saponins and phytosterols, etc 9,10 . Although some previous studies have reported the effects of cooking methods on fruits and vegetables, 2,5,11 studies about the comparison and effects of cooking methods on the polyphenols of quinoa in terms of their activities are yet to be seen.…”
Section: Introductionmentioning
confidence: 99%